Correlates of physical activity among depressed older people in six low‐income and middle‐income countries: A community‐based cross‐sectional study. (10th October 2017) - Vancampfort, Davy; Stubbs, Brendon; Veronese, Nicola; Mugisha, James; Swinnen, Nathalie; Koyanagi, Ai
Abstract : Objective: Despite the benefits of physical activity (PA) in older people with depression, many do not comply with the International PA guidelines. Thus, we investigated what factors influence PA participation among 915 community‐dwelling older adults (aged ≥65 years) with depression in 6 low‐income and middle‐income countries (LMICs). Methods: Cross‐sectional data were analyzed from the World Health Organization's Study on Global Ageing and Adult Health. The sample was restricted to those with DSM‐IV depression or receiving depression treatment in the last 12 months. PA was assessed by the Global Physical Activity Questionnaire. Participants were dichotomized into low (ie, not meeting 150 minutes of moderate PA per week) and moderate‐to‐high physically active groups. Associations between PA and a range of correlates were examined using multivariable logistic regressions. Results: The prevalence of low PA was 40.4% (95%CI = 34.8%–46.1%). After adjusting for age, sex, and country, larger household size and unemployment were significant sociodemographic correlates of low PA. Former smoking (vs never), anxiety, mild cognitive impairment (MCI), lower body mass index, bodily pain, asthma, chronic back pain, chronic obstructive pulmonary disease, hearing problems, stroke, slow gait, poor self‐rated health, higher levels of disability, and lower levels of social cohesion were identified as significant negative correlates of PA. Conclusions: The current data provide guidance for future interventions across LMICs to assist older people with depression engage in regular PA. The promotion of social cohesion may increase the efficacy of future public health initiatives, while from a clinical perspective, somatic co‐morbidities, MCI, pain, and slow gait need to be considered.